A clinical and radiographic evaluation of the efficacy of nanohydroxyapatite (Sybograf™) versus bioactive calcium phosphosilicate putty (Novabone®) in the treatment of human periodontal infrabony defects: A randomized clinical trial - Sravani Koduru; Suchetha Aghanashini; Sapna Nadiger; S M Apoorva; Divya Bhat; Bhavana Puvvalla (Contemporary Clinical Dentistry, 2019)
Aim: The aim of this study is to compare and to evaluate clinically and radiographically the bone regeneration and the amount of bone fill (BL) between nanocrystalline hydroxyapatite (Nc-HA) (Sybograf™) and bioactive synthetic NovaBone Putty in the treatment of intrabony component of periodontal osseous defects. Materials and Methods: Twenty sites in 20 patients, within the age range of 25–55 years, showing intrabony defects were selected and divided into Group I (Nc-HA) and Group II (Bioactive synthetic NovaBone Putty). All the selected sites were assessed with the clinical and radiographic parameters such as plaque index, gingival index, sulcus bleeding index, probing pocket depth, clinical attachment level, gingival recession, and radiographic BL. All the clinical and radiographic parameter values obtained at different intervals (baseline, 3, and 6 and 9 months) were subjected to statistical analysis. Results: A statistically significant reduction in pocket depth of 4.400 ± 0.843 mm (Group I), 3.800 ± 0.789 mm (Group II) and gain in clinical attachment level of 6.2 mm (Group I), 5.9 mm (Group II) were recorded at the end of the study. A slight increase in gingival recession was observed. The mean percentage changes in the amount of radiographic BL of Group II and Group I were significant, However, when compared between the groups, there is no significant difference in BL observed. Conclusion: Both the graft materials appear to have nearly comparable effects, with nanocrystalline hydroxyapatite (Sybograf™), displaying slightly superior effect over bioactive glass especially in relation to clinical parameters. However, long-term, controlled clinical trials are required to confirm these findings.